2020
DOI: 10.21203/rs.3.rs-34685/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Kidney Disease Diagnosis using Decision Tree Algorithms

Abstract: Chronic Kidney Disease (CKD), i.e., gradual decrease in the renal function spanning over a duration of several months to years without any major symptoms, is a life-threatening disease. It progresses in six stages according to the severity level. It is categorized into various stages based on the Glomerular Filtration Rate (GFR), which in turn utilizes several attributes, like age, sex, race and Serum Creatinine. Among multiple available models for estimating GFR value, Chronic Kidney Disease Epidemiology Coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Of all used machine learning algorithms, the most accuracy among all ML algorithms was related to the SVMs algorithm with 0.97. In our study the accuracy of SVMs algorithm among all of the applied ML algorithms was 0.82 which was lower than the study by Ilyas et al rate (15).…”
Section: Discussioncontrasting
confidence: 86%
“…Of all used machine learning algorithms, the most accuracy among all ML algorithms was related to the SVMs algorithm with 0.97. In our study the accuracy of SVMs algorithm among all of the applied ML algorithms was 0.82 which was lower than the study by Ilyas et al rate (15).…”
Section: Discussioncontrasting
confidence: 86%
“…In [5], The author analyzed how we can predict CKD (Chronic Kidney Disease) in its earliest stage and concluded that it can be done with J48 with an accuracy of 85. 5%.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The authors of [2] applied artificial neural networks for various algorithms. The KNN algorithm (K Nearest Neighbor) is also being employed, and the RFT algorithm is implemented.…”
Section: ░ 2 Related Workmentioning
confidence: 99%
“…It detects the label category relevant to the training document in a similar test document. This method is used in KNN [2] to classify things into object-based classes. Only the function is estimated locally, and all computations differ until classification.…”
Section: Decision Treesmentioning
confidence: 99%
See 1 more Smart Citation